Product-service system leanness assessment model: study of a UK manufacturing company - Elnadi, Moustafa; Shehab, Essam (Emerald, 2021)
Purpose Numerous leanness assessment models were developed for both manufacturing and service sectors. However, little research effort was made to provide an instrument that can be used to measure the leanness level of the product-service system (PSS). This paper aims to propose an index to assess the leanness of PSS in a UK manufacturing company. Design/methodology/approach The development of the assessment model was carried out through an iterative process. Commencing from existing literature on lean manufacturing assessment and lean service assessment, the initial model for assessing PSS leanness was developed. This initial model was refined via two consecutive phases. The first one includes semi-structured interviews with academic researchers involved in lean projects where their comments were considered. In the second phase, semi-structured interviews with several experts working in different UK manufacturing industries and involved in lean and continuous improvement projects were conducted to reach the final assessment model. After developing the model, the next step was identifying a suitable company for applying the model. The case company was selected because of its commitment to implement lean practices and its ability to participate in this study. After that, data was collected from the case company and the PSS leanness index was calculated using a multi-grade fuzzy approach. Finally, areas for further improvement were identified and the results obtained were validated. Findings The PSS leanness index computed for the case company indicates that the service offering process provided by the company is generally lean. Areas for further improvement were identified. Research limitations/implications This study focussed on a single case company and is based on the experts’ opinions; this may tend to be biased. However, future studies will be performed to multiple-case studies to enhance findings and more empirical research will be conducted to catch more insights into PSS leanness. Practical implications This paper provides guidelines to manufacturing companies’ managers for measuring the PSS leanness index and planning for the future. This index gives information regarding the degree of lean adoption in the service offering process and identifying the gap between the current PSS leanness level and the desired state. Originality/value The proposed model has been developed by the opinion of academicians and industry experts. The proposed model can provide guidelines and directions for managers for PSS leanness assessment.
Keywords: product-service system; leanness; Lean